Degradação do corante comercial disperse red1 por processo foto-Feton e avaliação ecotoxicológica - Leite, Laís da Silva [UNESP] (2014)
The textile industry produces highly colored effluents with complex composition and difficult degradation by biological processes due to the use of synthetic compounds of e high stability. Therefore it is necessary to develop efficient methods of treatment that be able to remove these compounds avoiding contamination of the receiving bodies of water. The present work studied the degradation of the dye Disperse Red 1 (DR1), in its commercially available form by photo-Fenton process. In order to evaluate the efficiency and monitor the formation of degradation products high performance liquid chromatography and mass spectrometry were used. The mineralization of samples was monitored by total organic carbon analysis . The concentration adopted for the degradation experiments was 0.2 mmol L-1 Fe(NO3)3 , 5.0 mmol L-1 H2O2 and 20 mg L-1 dye. Initially the pH was adjusted to 2.5 and the degradations were performed for 90 minutes. Under these conditions it was possible to mineralize 65% of the organic carbon content, degrade more than 99% of the dye and remove characteristic absorption after 30 minute experiment. The acute toxicity tests with the organism Daphnia similis showed that toxicity increased after 10 minutes of treatment, which was then reduced, no toxic values after 45 minutes of experiment. Mass spectrometry allowed to identify four degradation products, which contained the azo group in its structure. The maximum concentration of intermediates occurred after 10 minutes, which may be responsible for higher toxicity observed after this time of treatment. The results of this study showed that textile dyes, such as DR1 can be degraded by photo-Fenton process with complete removal of toxicity to Daphnia simillis microcrustacean and the ecotoxicological monitoring is essential for determining when the degradation process can be stopped.